(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Report is an important form of business communication. Generating and analysing reports is a routine task in every professional’s day-to-day activities. It is in fact hard to think of an organization where, as a professional, you would not be required to write some sort of a report. Reports are thus written to analyse a situation, to offer an alternative method of operation, to study the growth rate of a company, since reports acquire such inevitability in the professional world, it is mandatory for us to understand in detail how they are written, what their structure is, and what makes them effective.